Utilization of Injectable Drugs for Communicable and Non-communicable Diseases in Primary Healthcare: A Retrospective Study in Turkey - AKICI, AHMET (My University, 2023)
Objective: Primary care, which is often the first level of contact for patients with various communicable diseases (CDs) and noncommunicable diseases (NCDs), might exhibit patterns of injectable drug utilization different from hospitals. We aimed to examine injection prescribing to adults with CD or NCD in primary care.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; injectables; antibiotics; analgesics; primary care; thiocolchicoside.; TRENDS